ANALISIS UPAYA PEMERINTAH MALAYSIA DALAM MENDUKUNG SDG 13 MELALUI KEBIJAKAN CARBON CAPTURE, UTILITATION, AND STORAGE (CCUS) 2025 - Mufida Nurazizah; Tabah Maryanah (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2025)
ABSTRACT Climate change is a threat that has a major impact on sustainability and survival, thus requiring supportive and effective policy responses. Carbon Dioxide is one of the causes of climate change. Carbon emissions in Malaysia have shown an increasing trend in the last 5 years. As part of its efforts to support Sustainable Development Goal (SDG) 13, the Malaysian government has ratified the Carbon Capture, Utilization, and Storage policy outlined in ACT 870 to support Malaysia's 2050 carbon emission target. This study aims to analyze how the Malaysian government's efforts to support SDG 13 through ACT 870, with four aspects of the Robust principle in Environmental governance theory, which consist of the Legitimate, Connected, Nested, and Polycentric aspects. This study uses qualitative analysis by analyzing library information through official ACT 870 documents, Malaysian CCUS policy reports, and similar studies. The results of this study indicate that the ACT 870 CCUS 2025 Policy has met the legitimacy criteria in the normative, nested, and connected dimensions. However, the legitimacy criteria in the empirical and polycentric dimensions have not been met. Keywords: Climate Change; Environmental governance; Robust Principle; Carbon Emissions